Toxicity and synergistic activity of compounds from essential oils and their effect on detoxification enzymes against Planococcus lilacinus - Arokiyaraj, Charles; Bhattacharyya, Kangkanjyoti; Reddy, Sajjalavarahalli G. Eswara (Frontiers in Plant Science, 2022)
Mealybug, Planococcus lilacinus Cockerell, is a primary surface-feeding insect pest of fruit and flowering plants and also transmits plant viruses, resulting in economic crop loss. Inappropriate and recurrent use of pesticides for mealybug control results in resistance building and deleterious effects on humans and the environment. Essential oils are the most excellent choice for insecticides. Insecticidal activities of pure compounds of essential oils against P. lilacinus are not reported. The present study aims to study the insecticidal activities of some pure active compounds and their binary mixture’s action by topical application against P. lilacinus. Results showed that the pure compounds of L-limonene, β-myrcene, and ocimene revealed toxicity (each at LD50 = 0.37 µg/insect) after 96 h. The binary mixtures of geraniol + L-menthol and L-limonene + geraniol exhibited synergistic effects (each at LD50 = 0.03 µg/insect) after 96 h. The monoterpenes of ocimene and β-myrcene at the higher concentration of 5,000 ppm substantially inhibited the detoxification enzyme activities of AChE (0.93 and 0.78 mU/mg, respectively) and GST (2.19 and 7.29 nmol/min/ml, respectively) in P. lilacinus after 48 h. SEM analysis reported the significant anomalies on the morphology of abdominal cuticle, setae, and thoracic leg after 96-h treatment with ocimene at 1,250 ppm against P. lilacinus. Based on the results, the tested pure compounds and their combinations can be suggested for the control of mealybugs.